The Relationship Between Mother's Knowledge And Attitude With Low Birth Weight (LBW) In The Working Area Of Simpang Tiga Public Health Center - Hudnah Hudnah; Rahmayani -; Nova Arami (Jurnal Maternitas Kebidanan, 2026)
Pregnancy is a natural process that occurs over time. However, not all pregnancies and deliveries proceed physiologically; instead, they proceed pathologically, posing significant risks to the mother and fetus. One such risk is Low Birth Weight (LBW). Objective: This study aims to determine the relationship between maternal knowledge and attitudes and Low Birth Weight (LBW) in the Simpang Tiga Community Health Center (Puskesmas) work area. Method: This study was descriptive and analytical. Random sampling was used. Respondents were 40 postpartum mothers. The research instrument was a questionnaire consisting of 20 questions about personal matters and respondents' knowledge. The data were processed using the chi-square test with the help of SPSS. Results: Statistical analysis showed a relationship between maternal knowledge and LBW, with a P value of 0.00. There was also a relationship between maternal attitudes and LBW, with a P value of 0.00. Conclusion: Maternal knowledge and attitudes regarding LBW significantly influence infant mortality. So, if mothers have knowledge about LBW and are good at responding to LBW when it occurs, they can directly reduce infant mortality rates.